Las canciones del 15-M y su memoria. El sonido de un compromiso político - José Rafael Ramos Barranco (Cahiers de Civilisation Espagnole Contemporaine)
The 15-M movement meant much more than social mobilizations against the measures imposed by the government that led to a critical situation for thousands of Spanish families. It became an active starting point for a different way of understanding democracy that derived from the creation of citizen platforms to the emergence of political parties. In this paper we intend to analyze the role of songs in that movement and, above all, how the ideas of 15-M appear in contemporary Spanish song and through which artists. To do this, we study the visual and sound documents that exist about these mobilizations in 2011, while analyzing the songs of successful groups and artists who, without having shown their committed character in their early recordings and being an active part of the recording industry, have participated with a song to the memory of the 15-M demonstrations.